Lessons Learned at Community-University Institute for Social Research’s (CUISR) - Sanz, Penelope C. (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2024)
The University of Saskatchewan’s Community-University Institute for Social Research (CUISR) is celebrating its 25th anniversary very soon. Engaged Scholar Journal’s Penelope Sanz sat down with Isobel Findlay, University co-director of CUISR since 2011, to revisit the vision its founders set out 25 years ago and reflect on its achievements. The institute was established to facilitate community-university partnerships to engage in relevant and collaborative social research to gain a deeper understanding of Saskatchewan’s communities and to reveal opportunities to improve community quality of life.